An unexpected cause of recurrent pneumothorax - Rossi, Giulio; Farnedi, Anna; Davoli, Fabio; D'Agostino, Adolfo; Bizzarro, Tommaso; D'Angelo, Paride; Sargiacomo, Rita (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
The thoracic district is the most frequent visceral location of synovial sarcoma, generally involving lung and pleura as a large solid mass. We present herein a 57-year-old man with recurrent pneumothorax and a localized bulla at the lingula. The lesion was excised by a Video-Assisted-Thoracoscopic-Surgery (VATS) wedge resection and surprisingly consisted of a unilocular cyst with fibrous wall intermingled by a longitudinal proliferation of bland-looking, dense, monomorphic spindle cells diffusely expressing EMA, CD99, CD56 and focally staining with cytokeratins. Fluorescent in situ hybridization demonstrated the presence of SYT rearrangement and a diagnosis of pulmonary cystic monophasic synovial sarcoma was made. Only few similar cases have been reported in literature, mainly occurring in young male adults. A meticulous examination of all resected tissue from pneumothorax is the prerequisite to suspect this extremely challenging condition, while immuno- molecular studies are mandatory to achieve the correct diagnosis.